2022
DOI: 10.1108/ijse-12-2021-0731
|View full text |Cite
|
Sign up to set email alerts
|

Examining the interstate variations and interlinkage between water poverty and multidimensional poverty in India: evidence from household-level data

Abstract: PurposeThe purpose of the present study is to examine the inter-relationship between the multi-dimensional poverty and water poverty using household level data for Indian states.Design/methodology/approachA modified water poverty index (MWPI) for both rural and urban households was created using the five components approach and various quantifiable proxies. Principal component analysis (PCA) has been used for the construction of MWPI. Multidimensionality of poverty (MPI) is measured using the Alkire and Foster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
4
1
Order By: Relevance
“…Meanwhile, the ownership control variable, which is proxied by the percentage of the population with access to water, has no effect on the poverty level. This is different from the theory presented by Biltonen & Dalton (2003) and Pandey et al (2022) which states that there is a strong relationship between water availability and poverty. However, empirically the results of this study are in line with research Sumardjoko & Akhmadi (2019) which found that access to decent water had no effect on poverty alleviation.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…Meanwhile, the ownership control variable, which is proxied by the percentage of the population with access to water, has no effect on the poverty level. This is different from the theory presented by Biltonen & Dalton (2003) and Pandey et al (2022) which states that there is a strong relationship between water availability and poverty. However, empirically the results of this study are in line with research Sumardjoko & Akhmadi (2019) which found that access to decent water had no effect on poverty alleviation.…”
Section: Discussioncontrasting
confidence: 88%
“…The lack of access into water is associated with poverty (Biltonen & Dalton, 2003). In line with that, according to Pandey et al (2022), the availability of access to water has a significant impact on various dimensions of human life (Pandey et al, 2022) The last aspect is the prevention of harmful malpractice. Islam stipulates ethics that prohibits its people from taking actions that can harm themselves and others, including in the economy.…”
Section: Introductionmentioning
confidence: 99%
“…Source: World Development Indicator (WDI, 2021). (Pandey et al, 2022;Sugiharti et al, 2023;Ukpere & Slabber, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…But nowadays, it is widely accepted that urban poverty is multi-dimensional (Ayala et al. , 2011; Pandey et al. , 2022; Ravallion, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Urban poverty in India is recognized on the dimensions based on minimum calorific consumption. But nowadays, it is widely accepted that urban poverty is multi-dimensional (Ayala et al, 2011;Pandey et al, 2022;Ravallion, 2011). The critical dimensions of urban poverty include denied access to basic livelihood facilities like clean drinking water, food, sanitation and shelter and advanced rights such as quality education, primary healthcare and financial services (Chaigneau et al, 2019).…”
Section: Introductionmentioning
confidence: 99%